New anatomical and phylogenetic data on the late Neogene armadillo Macrochorobates scalabrinii (Chlamyphoridae, Euphractinae) - Barasoain, Darío Daniel (2020)
Fil: Barasoain, Darío Daniel. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.